Modifikasi Media Pembelajaran Bola Karet Terhadap Kemampuan Passing Bawah Bola Voli Siswa Smp - Bido Febrian Rahmat Khairul Surijat; Aria Kusuma Yuda Ryanto; Rahmat Iqbal (Jurnal Porkes, 2026)
This study aimed to determine the effect of rubber ball learning media modification on volleyball underhand passing skills among eighth-grade students at SMPN 15 Bekasi City. The problem underlying this research was the low underhand passing ability of students, largely due to discomfort and fear caused by using standard volleyballs. The study employed a quantitative approach using an experimental method with a One Group Pretest-Posttest Design. The population consisted of 347 students, while the sample comprised 37 students selected through cluster sampling. Data were collected using a validated and reliable underhand passing skills test (Cronbach's Alpha = 0.811) and documentation. Data analysis included descriptive statistics, the Shapiro-Wilk normality test, and the Paired Sample t-Test using IBM SPSS Statistics 25. The results indicated that the data were normally distributed and that there was a significant difference between students' underhand passing skills before and after the treatment (p = 0.000). The mean score increased from 27.81 in the pretest to 39.32 in the posttest, representing an increase of 11.51 points (41.4%). The use of rubber balls provided a safer and more comfortable learning experience, increased students' confidence, and improved their underhand passing skills. Therefore, rubber ball learning media modification is an effective alternative for enhancing volleyball underhand passing skills in physical education learning.